2007
DOI: 10.1002/mawe.200700210
|View full text |Cite
|
Sign up to set email alerts
|

Severe plastic deformation by linear flow splitting

Abstract: Due to the new linear flow splitting forming process the production of bifurcated profiles from sheet metal without lamination of material becomes feasible. The continuous production of such structures takes place incrementally in a modified roll forming machine. By producing those complex parts process-related changes in the material properties occur as a result of the cold forming. Thus, the assumption of homogeneous properties in the processed part is not valid and a reliable analysis of structural durabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 13 publications
(15 reference statements)
1
24
0
7
Order By: Relevance
“…Thus, the local strength can only be calculated from the hardness. Earlier investigations on the correlation of hardness and yield strength in bifurcated HSLA steel profiles processed by linear flow splitting led to an empirical equation derived from the well known Ludwik-equation [3]: Table 1 shows the good compliance between measured and calculated yield strength with a maximum deviation of less than 4%. Thus the strength in the region with the smallest grain size close to the flange surface can be calculated with adequate accuracy to ~1000 MPa.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the local strength can only be calculated from the hardness. Earlier investigations on the correlation of hardness and yield strength in bifurcated HSLA steel profiles processed by linear flow splitting led to an empirical equation derived from the well known Ludwik-equation [3]: Table 1 shows the good compliance between measured and calculated yield strength with a maximum deviation of less than 4%. Thus the strength in the region with the smallest grain size close to the flange surface can be calculated with adequate accuracy to ~1000 MPa.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier investigations have shown that linear flow splitting induces severe plastic strain which leads to the formation an ultrafine grained (UFG) microstructure in the regions of strongest plastic deformation, i.e. the splitting center and the flange surface [3]. In contrast to typical severe plastic deformation (SPD) processes as equal-channel angular pressing (ECAP) [4,5] or high pressure torsion (HPT) [5,6], linear flow splitting is characterized by inbuilt deformation gradients in the processing zone and a change in geometry of the semi-finished part.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations on HSLA steels have proven this method to be a suitable approximation [10]. Grain orientation measurements using EBSD were carried out at the corresponding positions of the hardness measurements in order to obtain textures and elastic properties.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly the formation of thin ultrafine-grained layers is achieved. Popular methods are the surface mechanical attrition treatment [13], linear flow splitting for flat products [14] or spin extrusion for tubes [1,15].…”
Section: Introductionmentioning
confidence: 99%